2002
DOI: 10.1051/gse:2002016
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the�growth curve of�Maine-Anjou beef cattle using�heteroskedastic random coefficients�models

Abstract: -A heteroskedastic random coefficients model was described for analyzing weight performances between the 100th and the 650th days of age of Maine-Anjou beef cattle. This model contained both fixed effects, random linear regression and heterogeneous variance components. The objective of this study was to analyze the difference of growth curves between animals born as twin and single bull calves. The method was based on log-linear models for residual and individual variances expressed as functions of explanatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Verbeke and Molenberghs [34] showed that this estimator is consistent as long as the mean is correctly specified in the model. In agreement with Robert-Granié et al [29], the results we obtained with this approach showed that, in most cases, the robust standard error was smaller than the naïve one.…”
Section: Model Selectionsupporting
confidence: 93%
“…Verbeke and Molenberghs [34] showed that this estimator is consistent as long as the mean is correctly specified in the model. In agreement with Robert-Granié et al [29], the results we obtained with this approach showed that, in most cases, the robust standard error was smaller than the naïve one.…”
Section: Model Selectionsupporting
confidence: 93%
“…Currently random regression models are being applied in the analysis of longitudinal growth in cattle (MEYER 1999, ALBUqUERqUE and MEYER 2001, ROBERT-GRANIé et al 2002, KREJčOVá et al 2007 sheep (LEWIS and BROTHERSTONE 2002, FARHANGFAR et al 2007, KESBI et al 2008 pig (HUISMAN et al 2002) and test-day lactation (JAMROZIK and SCHAEFFER 1997, OLORI et al 1999, KETTUNEN et al 2000, POOL and MEUWISSEN 2000, TAKIMA and AKBAŞ 2007 data. These models use polynomials in time to describe mean profiles with random coefficients to generate a correlation among the repeated observations on each individual (ROBERT-GRANIé et al 2002). This approach has the advantage of studying change and increases statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Currently RRM is being applied for genetic evaluation in growth trait such cattle (KREJCOVA et al, 2007;NESER et al, 2012;BOHLOULI et al, 2013), sheep (LEWIS and BROTHERSTON, 2002;GHAFOURI KESBI et al, 2008;ABEGAZ et al, 2010;KARIUKI et al, 2010;WOLC et al, 2011 ) and pig (HUISMAN et al, 2002) data. These models use polynomials in time to describe mean profiles with random coefficients to generate a correlation among the repeated observations on each individual (ROBERT GRANIE et al, 2002). Random regression models are better than multi-trait models, because they allow appropriate modeling of the genetic parameters by avoiding age pre-adjustment, feasibility of taking into account of specific environmental effects on the time of recording, decreasing of the generation interval, increasing of accuracy of breeding values, feasibility of calculating variance for every age and covariance among any pair of ages (MEYER, 2005;SCHAEFFER, 2004).…”
Section: Introductionmentioning
confidence: 99%